Global Photovoltaic Power Potential by Country - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2020)
Solar radiation is essentially a free resource available anywhere on Earth, to a greater or lesser extent. Solar PV power plants convert solar radiation into electricity. In the current era of global climate change, PV technology becomes an opportunity for countries and communities to transform or develop their energy infrastructure and step up their low-carbon energy transition. Until now, a global and harmonized assessment of country-level PV potential has not existed. This report aims to provide an aggregated and harmonized view on solar resource and PV power potential from the perspective of countries and regions, assuming a utility-scale installation of monofacial modules fixed mounted at an optimum angle, which has been the prevailing setup of a PV power plant.